The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/2586026
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Commercial Rice Husk Ash Additives on the Porosity, Mechanical Properties, and Microstructure of Alumina Ceramics

Abstract: A porous ceramic is made from composite materials which consist of alumina and commercial rice husk ash. This type of ceramics is obtained by mixing the commercial rice husk ash as a source of silica (SiO2) and a pore forming agent with alumina (Al2O3) powder. To obtain this type of ceramic, a solid-state technique is used with sintering at high temperature. This study also investigated the effects of the rice husk ash ratios on the mechanical properties, porosity, and microstructure. The results showed that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
1
9
0
1
Order By: Relevance
“…Square inserts of 12 mm × 12 mm × 4.76 mm made from oxide ceramics strengthened with silicon carbides were used for the conducted experiments. This kind of ceramic has a composite structure which was achieved by adding ceramic powdered SiC to the main powdered Al 2 O 3 in the form of whiskers [25][26][27][28][29][30][31][32]. The whiskers provide higher strength characteristics during sintering.…”
Section: Cutting Tools and Materials Being Processedmentioning
confidence: 99%
“…Square inserts of 12 mm × 12 mm × 4.76 mm made from oxide ceramics strengthened with silicon carbides were used for the conducted experiments. This kind of ceramic has a composite structure which was achieved by adding ceramic powdered SiC to the main powdered Al 2 O 3 in the form of whiskers [25][26][27][28][29][30][31][32]. The whiskers provide higher strength characteristics during sintering.…”
Section: Cutting Tools and Materials Being Processedmentioning
confidence: 99%
“…The incorporation of 10–15 wt% RHA as a partial replacement for cement enhances the strength and durability properties of self‐compacting cement (SCC). Ali et al 178. reported that 10–50 wt% of RHA added with alumina creates more porosity and new phases like cristobalite and corundum (an Al 2 O 3 ‐related phase), which increase the tensile strength and compressive strength of the concrete.…”
Section: Second Generation Agricultural Wastes and Their Usesmentioning
confidence: 99%
“…The UPV test was performed to obtain preliminary information on the internal structure or the compressive strength of the materials. It is the non-destructive test method, which is used to assess the quality of the solid materials [25]. In addition, the UPV values vary depending on both density and compositions of the materials.…”
Section: Ultrasonic Pulse Velocitymentioning
confidence: 99%